Effect of pre-incisional infiltration with bupivacaine liposome for postoperative pain in patients undergoing acoustic neuroma surgery: study protocol for a prospective, double-blind, randomized controlled study - Ran, Maolin; Song, Ailing; Liu, Xiaochen; Zhou, Yu; Chen, Feng; Cui, Qin; Xu, Hongjiao; Li, Jinbao (Frontiers in Medicine, 2025)
BackgroundPost-craniotomy pain, relatively common in neurosurgery, is often inadequately managed. Preincisional infiltration with ropivacaine provides effective analgesia for post-craniotomy pain, although its duration of action is limited. Liposomal bupivacaine, a long-acting local anesthetic, can provide analgesia for up to 72 h. However, there is a paucity of research on its efficacy in post-craniotomy analgesia. This study hypothesizes that pre-incisional infiltration with liposomal bupivacaine will demonstrate superior analgesic efficacy compared with ropivacaine in patients undergoing acoustic neuroma surgery.MethodsThis single-center, double-blind, randomized controlled study will recruit 112 patients scheduled to undergo acoustic neuroma surgery. We will compare the effects of liposomal bupivacaine and ropivacaine on postoperative pain when administered via preincisional infiltration before surgery. The primary outcome is the pain score at 24 h postoperatively. Secondary outcomes include the incidence of postoperative nausea and vomiting, amount of postoperative analgesic consumption, changes in vital signs before and after skin incision, and postoperative recovery scale.DiscussionThis randomized controlled trial aims to evaluate the superior effects of pre-incisional infiltration of liposomal bupivacaine on postoperative pain control in patients undergoing acoustic neuroma surgery. This may provide a more effective analgesic regimen for patients undergoing craniotomies.